ANALISIS TERHADAP TALAK DILUAR PENGADILAN PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Firmansyah, Viki; Lukmanul Hakim (Ahwaluna | Jurnal Hukum Keluarga Islam, 2025)
Divorce outside the court is a common occurrence in Indonesia, raising many questions about the legality and implications of divorce, both under Islamic law and positive law. The purpose of this study is to determine the concept of divorce outside the court, its implications, and its legality. The method used by the researcher is library research, where the data used are library data sourced from books, documents, journals, and other related literature. The results of this study are that the concept of divorce in Islamic law is not required to be carried out before the court because there is no evidence in the Quran or Hadith that states that divorce must be carried out before the court, however, in positive law, the concept of divorce must be carried out before a court hearing in accordance with applicable statutory provisions. The implications of divorce outside the court can cause legal problems and conflicts. For example, the wife cannot claim the right of mut'ah (mutah), cannot remarry another prospective husband because a divorce certificate from the court is required, even though they are still registered as a married couple administratively, even though they are divorced. She cannot claim joint property as regulated by law. The husband cannot remarry another prospective wife because they are still registered as a married couple, and cannot claim joint property as regulated by applicable regulations. For the children, they will not receive regular maintenance, both in terms of amount and time, especially if it does not meet the rules stipulated by law. Divorce outside the court in Islamic law is considered valid if it meets certain requirements, but must be prepared for all consequences resulting from an out-of-court divorce. While according to positive law, an out-of-court divorce is invalid because it does not comply with the procedures stipulated by law. Keywords: Divorce, Out-of-Court, Law, Islam, Positive.